CARIBE-MóVIL: de aquí, de allá y del más allá (2020)
In this audiovisual essay I explore the different possibilities of altering and constructing memory about the territory. Through a constant displacement through different geographical points of the Colombian Caribbean, I elaborate a fictional cartography from the understanding of the archive, understood as the dialogue between oralities, visualities and materialities that acquire different forms.From my concern for understanding how movement, as a way of life and inhabited space, conditions my being Caribbean, I approach and invite myself to explore those momentary, fragmented and imagined spaces, where the routes -fluvial and terrestrial and non-place- are understood as border and infinite spaces that allow other ways of constructing memory, from the physical and interior landscape. In this sense, through the audiovisual journey I seek to dismantle the idea of the Caribbean rooted in the collective imaginary to think about other identities, images and experiences.